OBSERVING THE INDONESIAN HOUSE OF REPRESENTATIVES' PERFORMANCE - Azed, Abdul Bari (Indonesia Law Review, 2014)
DPR fulfilled mandate of the people, one of its way is through legislation function, namely formed Act with an agreement with the President. Expectations of the people filled with less than optimal by DPR caused by the performance of the parliament in the field of legislation which was less than satisfactory because did not fulfill the Prolegnas target which they had made themself. This condition caused the functions of DPR as parliament not fully carried out in encouraging people prosperity and developing the country. Hence, it is important to do a series of policy and concrete steps to minimize problems that involve parliament as well as to promote better performance legislation function in the House of Representatives.